The phlogiston theory of rock mass Classification: Philosophical and mathematical critique of ordinal data usage - Junzhe Liu; Yu Feng; Yuyong Jiao (Rock Mechanics Bulletin, 2025)
The widespread use of rock mass classification systems in engineering practice relies on mathematical operations and assumptions that violate fundamental principles of measurement theory. This paper presents a critical analysis of current classification methodologies, focusing on the Rock Mass Rating (RMR), Q-system, and Geological Strength Index (GSI), drawing parallels with historical scientific misconceptions such as the phlogiston theory. Through detailed examination of measurement theory principles and their application to geological characterization, we demonstrate that these classification systems contain inherent flaws in their treatment of ordinal data and parameter independence. The paper identifies four critical issues: the invalid summation of ordinal ratings in the RMR system, the inappropriate multiplication and division operations in the Q-system, the unjustified visual interpolation in the GSI system, and the universal problem of assumed parameter independence. Through examination of measurement theory principles and their application to geological characterization, we demonstrate that current classification systems violate basic mathematical rules in their treatment of ordinal data and parameter independence. The implications of these violations extend beyond theoretical concerns, affecting practical engineering decisions and risk assessment. We also illustrate how these theoretical flaws manifest in practice and propose directions for developing more theoretically sound approaches to rock mass characterization. This critical analysis aims to initiate a necessary dialogue about the future of rock mass classification in engineering practice.